The Influence of Academic Advisors on Students' Learning Motivation - Sumarni, Sumarni; Muhammad Nur; Muhammad Nasir; Erviana Abdullah; Besse Herlina; Besse Sulfiani (NAJAHA, 2025)
This study aims to determine the effect of Academic Advisory Lecturers on Learning Motivation of Class 2019 Students of the Faculty of Teacher Training and Education. This study uses a quantitative approach with a correlation test method involving two variables, namely Academic Advisory Lecturers (X) and Student Learning Motivation (Y). The sample in this study amounted to 89 people who were students of the Class of 2019 Faculty of Teacher Training and Education. Based on the results of the study, it can be concluded that there is an influence of academic advisory lecturers on the learning motivation of Class 2019 students of the Faculty of Teacher Training and Education, Puangrimaggalatung University, this is in accordance with the results of the hypothesis shown by the t arithmetic value of 7.074 > t table 1.663. The magnitude of the influence is 32.4%, and the remaining 76.6% is influenced by other factors outside the study. For Academic Advisory Lecturers to provide motivation and direction in lectures and or outside lectures so that students can increase their learning motivation so that they are enthusiastic and have a high fighting spirit in taking education. Although academic advisory lecturers only have a small effect on learning motivation, the existence of Academic Advisory Lecturers for Students is still a very important factor.